2013
DOI: 10.3168/jds.2013-6665
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and lactational performances of late-lactation dairy goats under heat stress conditions

Abstract: Eight Murciano-Granadina dairy goats in late lactation were exposed to different ambient conditions, using metabolic cages in a climatic chamber. The experimental design was a crossover (2 periods of 35 d and 4 goats each) and conditions were (1) thermal neutral (TN; 15 to 20 °C day-night) and (2) heat stress (HS; 12-h day at 37 °C and 12-h night at 30.5 °C). Humidity was maintained at 40% and light-dark was constant (12-12h). The forage:concentrate ratio was adjusted daily for maintaining similar value in TN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
125
4
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 29 publications
28
125
4
6
Order By: Relevance
“…The negative correlations between temperature and some short-chain FAs are in agreement with studies showing the reduction in the FAs synthesised from the breast (de novo) as a result of the increase of temperatures, usually combined with a reduced intake of feed (Hamzaoui et al 2013). Some authors have suggested that, to cope with the lack of energy due to decreased feeding, goats do not mobilise body fat, but change the rumen fermentation and rumen volatile FA profile (Salama et al 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The negative correlations between temperature and some short-chain FAs are in agreement with studies showing the reduction in the FAs synthesised from the breast (de novo) as a result of the increase of temperatures, usually combined with a reduced intake of feed (Hamzaoui et al 2013). Some authors have suggested that, to cope with the lack of energy due to decreased feeding, goats do not mobilise body fat, but change the rumen fermentation and rumen volatile FA profile (Salama et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…The decrease in feed intake could be the adaptive mechanism to produce less body heat (Marai et al 2007). Since in lactating animals most of the blood glucose is used by the breast for the lactose synthesis, it could be speculated, according to Hamzaoui et al (2013), that the reduction in lactose secretion is a strategy to maintain stable glycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In goats, if the THI is below 65 or above 75, the animal may experience thermal stress (Hamzaoui et al 2013). In the present study, the AT and THI were higher than the thermoneutral zone in the afternoon hours of the HDS and RAS, suggesting that the goats experienced heat stress in these seasons.…”
Section: Meteorological Parametersmentioning
confidence: 37%
“…Certainly the thermolysis mechanisms, especially latent heat loss, were triggered to maintain the animals' normal temperatures, confirming their homeothermic capacity. Hamzaoui et al (2013) reported that animals keep under heat stress condition into climatic chambers, presented the highest values of RT and RR during the first week, but after this period were observed slight decreasing of these variables, which indicates a partial adaptation to the heat stress conditions. These results could explain the low variability of RT and RR of animals among environmental conditions (from groups 1 to 5), possibly animals were acclimated to high radiation and air temperature in which they were exposed over the years.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, maintaining RRs high for a long time can cause some physiological disturbance, such as acid-basic disequilibrium (Srikandakumar et al 2003;Hamzaoui et al 2013). However, we found that, considering the natural environmental conditions analysed, there were no changes in stress response parameters, such as RR and RT, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%